Binary optical switch and programmable optical logic gate based on the integration of GaAs/AlGaAs surface-emitting lasers and heterojunction phototransistors - Vawter, G. A., author; Chalmers, S. A., author; Zolper, J. C., author; Lear, Kevin L., author; Zilko, John Leon, author; Adams, A. C., author; Leibenguth, R. E., author; Cheng, Julian, author; Lu, Yin-Chen, author; Zhou, Ping, author; Lu, Bo, author; IEEE, publisher (Colorado State University. Libraries, 1994)
Optical switches based on GaAs/AlGaAs vertical-cavity surface-emitting lasers and heterojunction phototransistors are combined monolithically into new switching configurations that perform optical logic and spatial routing in a dynamically programmable manner. Using simple voltage control, many different logic and routing configurations, including AND and OR gates with variable fan-out, can be implemented using the same hardware.
Keywords: optical logic; optical switches; III-V semiconductors; aluminium compounds; electro-optical devices; phototransistors; semiconductor lasers; gallium arsenide; integrated optics; semiconductor switches